Recent Advances in Chronotherapy Targeting Respiratory Diseases - Keshav Raj Paudel; Saurav Kumar Jha; Venkata Sita Rama Raju Allam; Parteek Prasher; Piyush Kumar Gupta; Rahul Bhattacharjee; Niraj Kumar Jha; Sukriti Vishwas; Sachin K. Singh; Jesus Shrestha; Mohammad Imran; Nisha Panth; et al. (MDPI AG, 2021)
Respiratory diseases contribute to a significant percentage of mortality and morbidity worldwide. The circadian rhythm is a natural biological process where our bodily functions align with the 24 h oscillation (sleep-wake cycle) process and are controlled by the circadian clock protein/gene. Disruption of the circadian rhythm could alter normal lung function. Chronotherapy is a type of therapy provided at specific time intervals based on an individual's circadian rhythm. This would allow the drug to show optimum action, and thereby modulate its pharmacokinetics to lessen unwanted or unintended effects. In this review, we deliberated on the recent advances employed in chrono-targeted therapeutics for chronic respiratory diseases.